Why sponge planet? Discussions on land-based, water-driven solutions - Spirn, Anne Whiston; Schellnhuber, Hans Joachim; Daigger, Glen T.; Fu, Jun; Childs, Peter; Sedlak, David; Head, Peter; Ravasi, Timothy; de Meulder, Bruno; Shannon, Kelly; Dultzin, Daniel; Sosa, Fabiola; et al. (Higher Education Press, 2025)
The recent Nature Water article, “To Solve Climate Change, We Need to Restore Our Sponge Planet,” by Kongjian Yu, Erica Gies, and Warren W. Wood, makes a compelling case for recalibrating climate strategies to prioritize the water cycle alongside reducing carbon emissions. The authors highlight how human activities—agriculture, urbanization, and industrialization—have degraded 75% of the earth’s land, severely disrupting natural water systems. This degradation diminishes the planet’s capacity to regulate temperature through water vapor, cloud formation, and the hydrological cycle, further accelerating climate instability.